Peran Guru Bimbingan Dan Konseling Dalam Pengembangan Potensi Anak Berkebutuhan Khusus di SDIT Armaniyah - Nenda; Sarwo Edy; Listian Indriyani Achmad; Saiful Muktiali (Institut Agama Islam Negeri Curup, 2025)
Every human being is born in a state of nature and perfection, behind that perfection there are differences from one to another. To make that difference into something positive and beneficial, humans need an education process which is a conscious effort by each person to form and build a good personality both physically and mentally so that they understand the aspects of ngerti-ngroso-ngelakoni which are accompanied by tekat-ucap-lampah. Among these educations, there is inclusive education designed for children with special needs (ABK), this is also implemented by SDIT Armaniyah which is located in Serang Baru, Bekasi. The research method used is qualitative-descriptive which produces data through the process of interviews, observations, documentation by studying phenomena that occur naturally. Data obtained using purposive sampling with the 3M standard. In the process, each inclusive education program is not only implemented by educational institutions. However, it also involves guidance and counseling teachers to accompany inclusive students in developing their potential. The services provided are: (1) psychoeducational services; (2) special class services; (3) and home visit services. The stages of the mentoring process carried out include: (1) identification; (2) instrument design; (3) program implementation; (4) and monitoring. The success of inclusive education is not only viewed from the aspect of educational institutions, but culture, policies, politics, and other supporting resources also have a great influence.